A Review: Study on Spent Garnet as Construction Material - Yusoff, A R M; Mokhatar, S N; Budiea, A M A; Hakim, S J S (International Journal of Integrated Engineering, 2022)
Numerous environmental problems are mitigated by natural resource depletion, with yearly global use of nearly 25 billion tonnes, including aggregates. Fast industrial growth has witnessed the ever-increasing exploitation of sand from rivers for various construction resolves, which caused an over-exploitation of rivers’ beds and disturbed the eco-system. This problem is also related to the amount of waste produced each year. The volume of waste is estimated to rise, reducing available space and causing pollution. Many studies have discovered inventions and ideas to deal with this situation. Some researchers use the spent garnet in a concrete mix as a partial fine aggregate replacement. The alternative in a concrete mix depends on the properties of the spent garnet that is used and its appropriateness. In this paper, a critical review of spent garnet were discussed in detail.